Pengelolaan Konten Media Sosial Akun Instagram @soekarnohattaairport Dalam Meningkatkan Customer Engagement - Nicky, Caesaria Chantikan; Lestari, Martha Tri (Jurnal Pustaka Komunikasi, 2025)
Soekarno-Hatta Airport is a public institution that plays an important role in the transportation sector and the national economy, having been in operation since 1985. The Instagram account @soekarnohattaairport has shown rapid growth with its ability to reach 948,007 accounts and an engagement rate of 3.02%. This research aims to understand how the social media content management of Soekarno-Hatta Airport’s Instagram account enhances customer engagement. The study employs The Circular Model of SoMe and the theory of Social Media and Customer Engagement. The research uses a descriptive qualitative method, with data collection conducted through observation, document studies, and interviews with the Assistant Manager of Public Relations and the Public Relations Officer from the Branch Communication unit of Soekarno-Hatta Airport, experts in Company Branding and Social Media, as well as followers of the @soekarnohattaairport Instagram account. The results of the study indicate that the management of the @soekarnohattaairport Instagram account as a public communication medium consists of four stages: share, optimize, manage, and engage. Enhancing customer engagement is carried out through four stages: consumption, curation, creation, and collaboration. However, there are several areas that need improvement by the account managers, such as the use of social listening tools for media monitoring activities, the use of live streaming features to further increase interaction, and improving consistency in responding to audience comments.